Characterization of volatile constituents and odorous compounds in peach (Prunus persica L) fruits of different varieties by gas chromatography–ion mobility spectrometry, gas chromatography–mass spectrometry, and relative odor activity value - Sun, Ping; Xu, Bing; Wang, Yi; Lin, Xianrui; Chen, Chenfei; Zhu, Jianxi; Jia, Huijuan; Wang, Xinwei; Shen, Jiansheng; Feng, Tao (Frontiers in Nutrition, 2022)
In order to find the flavor features of Chinese peaches, the comparative diversity of peach fruit volatiles across 10 peach samples of three varieties (honey peach, yellow peach, flat peach) was done in this work. The volatile components of peach fruits were analyzed and identified by gas chromatography-ion mobility spectrometry(GC-IMS)combined with gas chromatography-mass spectrometry(GC-MS), and the main flavor components of peach fruit were determined by relative odor activity value(ROAV) and principal component analysis(PCA). A total number of 57 volatile components were detected by GC-IMS, including 8 aldehydes, 9 alcohols, 8 ketones, 22 esters, 2 acids, 2 phenols, 2 pyrazines, 1 thiophene, 1 benzene, and 2 furans. The proportion of esters was up to 38.6%. A total of 88 volatile components were detected by GC-MS, among which 39 were key aroma compounds with ROAV≥1. The analysis results showed that alcohols, ketones, esters and aldehydes contributed the most to the aroma of peach fruit; PCA analysis demonstrated that (E,E)-2, 6-nonadienal, n-hexanol, β-ionone and hexyl hexanoate were the key contributors to the fruit aroma. A reference for future directional cultivation and breeding could be provided by this study through evaluating the aroma quality of the peach at the cultivar level. The possible reasonable application of these peach fruits pulp will be guided through these research.